Afro-Cuban Cyberfeminism: Love/Sexual Revolution in Sandra Álvarez Ramírez’s Blogging - Judith Sierra-Rivera (Latin American Research Review, 2018)
This essay focuses on the dynamics of (dis)embodiment between national love and the body of the black woman in Cuba. This very discussion lies at the center of Sandra Álvarez Ramírez’s blog 'Negra cubana tenía que ser', where the black woman’s body becomes an ideal in itself. Álvarez Ramírez’s intellectual interventions impress this body with love and assemble a community whose members share the black feminist goal of a sexual (polyamory) revolution. I propose that 'Negra cubana'’s revolutionary matrix resides in the blog’s networking: a cyberfeminist agenda to connect Cuban black women’s voices with other voices around the world. Contrary to the utopian promise of the Cuban Revolution, 'Negra cubana'’s black feminist promise is that of enactment in the present—in both physical and virtual realms. Resumen Este ensayo se centra en las dinámicas de (des)materialización que ocurren entre el amor nacional y el cuerpo de la mujer negra en Cuba. Esta discusión es la que precisamente guía el blog 'Negra cubana tenía que ser', de Sandra Álvarez Ramírez, en el que el cuerpo de la mujer negra deviene un ideal en sí mismo. Las intervenciones intelectuales de Álvarez Ramírez imprimen amor sobre este cuerpo y, a la vez, conforman una comunidad que comparte una meta afro-feminista: una revolución sexual (de poliamor). Propongo que la matriz revolucionaria de 'Negra cubana' reside en la interconectividad del blog, es decir, en una agenda ciberfeminista que conecta voces de mujeres negras de Cuba con otras alrededor del mundo. Contrario a la promesa utópica de la Revolución Cubana, la promesa afro-feminista de 'Negra cubana' se ejerce en el presente, tanto en el mundo material como en el virtual.